Strategies for effective supplemental instruction to enhance academic perfomance of first year Accounting students - Mokhampanyane, Matsolo Claurina (Technium Social Sciences Journal, 2021)
Substandard academic performance of first year accounting students is a challenge experienced in certain institutions of higher learning worldwide. Literature shows that institutions have put in place interventions to mediate the underperformance and failure rate to improve academic performance. Supplemental instruction (SI) programmes, for example, were initiated to minimise deteriorating academic performance. However, challenges persist in implementing supplemental instructional intervention effectively. Therefore, this paper explores strategies for effective SI to enhance academic performance of first year accounting students. The qualitative research method was undertaken using an interpretivist approach. The participants for the study consisted of one supplemental instruction coordinator, two SI student leaders, two Accounting lecturers, and two first year accounting students. All participants were purposively sampled from the faculty of Management Sciences at a selected university for the study. Data collection by means of interviews was employed. A thematic analysis was assumed to sort, interpret, and analyse the collected data, as they include the replication of categorised objectives. The findings of the study reveal that challenges hindering effective implementation of supplemental instruction on academic performance includes inadequate content knowledge of SI leaders, timetable clashes, lack of timely feedback, and incompetency in leading others. These are the major challenges; on the other hand, strategies to solve the problem were retraining of SI student leaders and planning of their sessions and timetable.